Health-related marketing messages on product labels of commercial infant and toddler food packaging in Australia: a cross-sectional audit - Aimee L Brownbill; Lucy Simmonds; Anthea Zee; Merryn J Netting (BMJ Publishing Group, 2021)
Background Proper nutrition in early childhood is essential to ensure optimal growth and development. Use of 'better-for-you' features on food packaging position products as healthier for children. This study aims to systematically explore the use of better-for-you labelling on infant and toddler food packaging.Methods A cross-sectional audit of health and nutrition claims, text and images used as 'better-for-you' features present on infant and toddler food packaging. Data on infant and toddler food packaging were collected from five large grocery stores in Adelaide, Australia in 2019. The content of 282 unique commercial products (n=215 infant foods, n=67 toddler foods) were analysed for explicit and implicit features positioning them as better-for-you, including health and nutrition claims as well as text and images representing 'natural.'Results At least one feature of better-for-you positioning was identified on all food packaging coded. All products had characteristics coded as 'natural'. Almost one-fifth (17%) of the products included statements in addition to mandatory allergen labelling that their products were 'free from' certain allergens, or gluten. One-third of the labels had statements related to enhancing development of taste, oro-motor skills and other aspects of childhood development. Of the fruit and vegetable-based infant foods displaying a sugar statement suggesting a low sugar content, 85% were sweetened with fruit puree.Conclusions The use of better-for-you features on infant and toddler food packaging is common and pervasive. Allergen-free and developmental claims are being used to position infant and toddler foods as better-for-you. Regulation of toddler food products separately from adult food is required, as is tighter regulation of the appropriate use of sugar and fruit puree statements on infant and toddler food packaging.